Prediction Method for Rain Rate and Rain Propagation Attenuation for K-Band Satellite Communications Links in Tropical Areas - Baso Maruddani; Adit Kurniawan; Sugihartono Sugihartono; Achmad Munir (Journal of ICT Research and Applications, 2014)
This paper deals with the prediction method using hidden Markov model (HMM) for rain rate and rain propagation attenuation for K-band satellite communication link at tropical area. As is well known, the K-band frequency is susceptible of being affected by atmospheric condition, especially in rainy condition. The wavelength of K-band frequency which approaches to the size of rain droplet causes the signal strength is easily attenuated and absorbed by the rain droplet. In order to keep the quality of system performance for K-band satellite communication link, therefore a special attention has to be paid for rain rate and rain propagation attenuation. Thus, a prediction method for rain rate and rain propagation attenuation based on HMM is developed to process the measurement data. The measured and predicted data are then compared with the ITU-R recommendation. From the result, it is shown that the measured and predicted data show similarity with the model of ITU-R P.837-5 recommendation for rain rate and the model of ITU-R P.618-10 recommendation for rain propagation attenuation. Meanwhile, statistical data for measured and predicted data such as fade duration and interfade duration have insignificant discrepancy with the model of ITU-R P.1623-1 recommendation.